Invasive species - Adams, Ellery (Hanover Square Press, 2026)
"The women in Cold Harbor all have something to prove, and they'll have to do it in a world full of monsters. Something's not right in Cold Harbor--more so than usual. While this sleepy small town has seen its fair share of monsters in cheating husbands and leering bosses, none are as hungry as Mrs. Smith. The mysterious resident has finally emerged from her crumbling mansion on the hill, mesmerizing the townspeople with her beauty. Her secret? Nine human sacrifices tofeed her immortality. Natalie Scott is more worried about Mrs. Smith blocking her first real estate sale--the one that will take her from stay-at-home mom to working woman extraordinaire. She's eager toprove herself in a world where the social mores of 1980s suburbia reign, where she's expected to keep a magazine-perfect home and raisebeautiful children, all while sticking to her husband's budget. Natalie's two best friends are facing their own demons, and Mrs. Smith and her deep, dark woods are an easy scapegoat for everyone's problems. But Natalie's twelve-year-old daughter, Jill, and her Icelandichousekeeper, Una, can sense something deeper at play. Armed with library books and a whole lot of grit, Jill and Una team up to save the town once and for all. But as the rest of Cold Harbor sinks into anger, fear, and jealousy, they'll have to confront the question: What does it really mean to be a monster?"--